Up-to- date summary about human immunodeficiency virus and acquired immunodeficiency syndrome - Raysy Sardiñas Ponce (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
In spite of the efforts and initiatives developed worldwide, the amount of people living with the human immunodeficiency virus (HIV) increases daily as well as the amount of people who die due to the acquired immunodeficiency syndrome (AIDS). In our country, all these initiatives have achieved an important decrease in mortality rate due to the acquired immunodeficiency syndrome and an improvement in the quality of life of all those who live with the human immunodeficiency virus . Nevertheless, the epidemic still increases annually, although at a slower pace locating Cuba among the countries with the lowest international prevalence. This review was carried out because of the updated and highlighting importance of the topic for the academic formation of the health staff and it was aimed at summarizing up-to-date as a teaching support in the formation of the future health professionals.